Asymmetries in reciprocal baroreflex mechanisms and chronic pain severity: Focusing on irritable bowel syndrome. Issue 2 (22nd August 2017) - Davydov, D. M.; Naliboff, B.; Shahabi, L.; Shapiro, D.
Abstract: Background: Objective measures of pain severity remain ill defined, although its accurate measurement is critical. Reciprocal baroreflex mechanisms of blood pressure (BP) control were found to impact differently on pain regulation, and thus their asymmetry was hypothesized to also connect to chronic pain duration and severity. Methods: Seventy‐eight female patients with irritable bowel syndrome (IBS) and 27 healthy women were assessed for IBS severity and chronicity, negative affect, and various measures of resting autonomic function including BP, heart rate and its variability (HRV), baroreceptor‐sensitivity to activations and inhibitions, gains of brady‐ and tachy‐cardiac baro‐responses, gains of BP falls/rises, and BP start points for these spontaneous baroreflexes. Key Results: IBS directly and indirectly (through increased negative affect) was associated with asymmetry between baroreceptor activations/inhibitions compared to symmetrical baroreflex reciprocity in the healthy women. In the IBS group, independently of specific IBS symptoms, pain chronicity was associated with (i) decreased BP falls coupled with either (a) decreased tachycardia associated with lower disease severity (earlier "pain resilience" mechanism), or (b) decreased bradycardia associated with higher disease severity (later "pain decompensation" mechanism), or (ii) increased BP start point for baroreceptor activations coupled with either (a) BP increase (delayed "pain adaptation" mechanism) or (b) affect‐related HRV decrease (delayed "pain aggravation" mechanism). Conclusion and Inferences: We anticipate the findings to be a starting point for validating these autonomic metrics of pain suffering and pain coping mechanisms in other chronic pain syndromes to suggest them as biomarkers of its severity and duration for profiling and correct management of chronic pain patients. Abstract : Spontaneous cardiac baroreflex responses were obtained by continuous recordings of systolic blood pressure and electrocardiogram in groups of control subjects and patients with irritable bowel syndrome (IBS) during resting baseline recording. Severity of abdominal pain in patients with IBS determines an asymmetrical reciprocity in baroreflex responses to falls and rises of systolic blood pressure that indicates pain resilience, pain decompensation, pain adaptation, and pain aggravation mechanisms related to the disease duration. These findings could help to improve and personalize treatment of the IBS.